The savvy investor's guide to avoiding pitfalls, frauds, and scams - Baker, H. Kent; Nofsinger, John R.; Puttonen, Vesa (The Savvy investor's guide, 2020)
Are you an investor facing an obstacle you dont know how to overcome? Are you ready to invest, but not sure how to reduce your risks? There are two important things you must do to be a savvy investor: make good investment decisions and avoid costly mistakes. As important as good investments are, one bad mistake can ruin the result of all your good decisions. In the second book in The H. Kent Baker Investments Series, investing experts H. Kent Baker, John R. Nofsinger, and Vesa Puttonen offer an insightful guide on avoiding those detrimental missteps. The Savvy Investor's Guide to Avoiding Pitfalls, Frauds and Scams explores the common pitfalls that investors face. Highlighting important issues when investing especially in common stocks and mutual funds, they explore the psychological biases of investors that can cause you to be your own worst enemy. Finally, they look at frauds and scams, and how to protect yourself from dishonest people wanting to profit at your expense. If you feel unprepared to face the risks of investing, Baker, Nofsinger, and Puttonen provide this essential guide to arming yourself against devastation on your path to becoming a savvy investor.